2020
DOI: 10.1109/tgrs.2020.2975458
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Slant Wet Delays From One GPS Receiver as a Series Expansion With Respect to Time and Space: Theory and an Example of Application for the Tahiti Island

Abstract: Traditionally, the modeling of the water vapor contents of the atmosphere is done through the estimation of precipitable water (PW)-the integrated value of the mass of water vapor over a vertical column expressed in millimeter equivalent height. This modeling method is justified by the fact that, to a high degree of approximation, the atmosphere can be seen as the stacking of horizontal layers, including water vapor, over distances larger than the height of the tropopause. Nevertheless, the cycle of the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The mapping function concept was first derived for astronomy and positioning applications [9], considering integrated quantities along the radio ray path. This approach needs to be extended to take into account both dry and wet variations in refractivity along the ray path caused by the turbulent atmosphere [55] to meet the requirements of modern applications such as GNSS meteorology and data assimilation in numerical weather models. The Saastamoinen ZHD model assumes atmospheric hydrostatic equilibrium, while the mapping function assumes an azimuthal isotropous atmosphere with smooth variation over time.…”
Section: Resultsmentioning
confidence: 99%
“…The mapping function concept was first derived for astronomy and positioning applications [9], considering integrated quantities along the radio ray path. This approach needs to be extended to take into account both dry and wet variations in refractivity along the ray path caused by the turbulent atmosphere [55] to meet the requirements of modern applications such as GNSS meteorology and data assimilation in numerical weather models. The Saastamoinen ZHD model assumes atmospheric hydrostatic equilibrium, while the mapping function assumes an azimuthal isotropous atmosphere with smooth variation over time.…”
Section: Resultsmentioning
confidence: 99%
“…Eq. ( 1) is sufficient by itself to model these slant (extra) delays, as evidenced by tomography applications and the statistical analysis of these delays [69]. The zenithal total delays have proven to have a physical meaning, as they are related to the modeling of PW through an a priori model of the "dry" atmosphere and a proportional correspondence to zenithal wet delays.…”
Section: Beyond Zenithal Delays and Gradientsmentioning
confidence: 99%
“…(1)? The response is a careful yes [69]. Strictly speaking, a mapping function defines, from the point of view of differential geometry, a time-evolving coordinate chart that is a non-orthogonal system of coordinates made of the refracted elevation at ground level, the length along the bended ray, and the azimuth.…”
Section: Beyond Zenithal Delays and Gradientsmentioning
confidence: 99%
“…It is known that water vapor is the most significant greenhouse gas in the atmosphere [3], and its changes can serve as an indicator of cloud formation and precipitation. One significant feature is that variations in moisture content can be caused by other external factors of temperature change (for example, due to a sharp change in the content of other greenhouse gases).…”
Section: Introductionmentioning
confidence: 99%
“…One significant feature is that variations in moisture content can be caused by other external factors of temperature change (for example, due to a sharp change in the content of other greenhouse gases). The works [3][4][5][6][7][8] show the relationship between changes in the mass of vertically integrated water vapor (IWV) and changes in temperature. It has been found that an increase of the temperature of 1 K leads to an increase in IWV of about 5-7%.…”
Section: Introductionmentioning
confidence: 99%